THE CONTENT OF FATTY ACIDS IN INDONESIA’S FISH OIL - Indra T Maulana; Sukraso Sukraso; Sophi Damayanti (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2014)
Study of fatty acid content was conducted in six Indonesian fish oils taken from Surabaya, Sorong, Garut, Banyuwangi, and  fish oil standard. The acid and peroxide values were a main parameters which affecting the quality of the fish oil. These parameters were set using the method stated on the SNI No. 01-3555-1998. The oil containing omega-3 such as EPA and DHA is beneficial for health. The study of fatty acid content in six fish oils were analyzed by GCMS Shimadzu QP 2010 ULTRA with FID Detector. RTX-5 were used as a column (diphenyl dimethyl polysiloxane  as a solid buffer, size length 30 m, diameter 0,25 mm, and He as a gas mobile phase).  The results showed that acid values for oil 1, 2, 3, 4, 5, and 6 were 0.55%, 0.50%, 0.48%, 0.55%, 0.48%, and 0.58%, respectively. While the peroxide values were 5.67, 4.72, 4.45,5.01, 4.85, and 5.27 meq/kg, respectively. GCMS analysis showed that fish oil 1, 2, 3, and 4  very dominant containing squalene of  29.45%, 32.34%, 21.07%, and 43.49%, respectively. While oil 6 contained EPA of 8.97% and DHA 6.56%, and that was the highest compared with other oils. However, oil 6 also contained a trans fatty acids i.e., elaidic acid of 26.8% and trans-13-docosanoic acid of 0.9%. For comparison, natural oil 5 was rich of linoleic acid  (39.58%).  The GCMS's analysis results proved that the oil 6 made from lemuru had a big potency to be developed for an Indonesian fish oil export comodity. Keywords: fish oil, EPA, DHA, squalena, GCMS, acid value, peroxide value